The application of inferior vena cava filters in orthopaedics and current research advances - He, Jingchao; Wang, Zhitao; Zhou, Yue Xin; Ni, Hongbo; Sun, XiaoHanu; Xue, Jian; Chen, Shanshan; Wang, Shuai; Niu, Meng (Frontiers in Bioengineering and Biotechnology, 2022)
Deep vein thrombosis (DVT) is a common clinical peripheral vascular disease that occurs frequently in orthopaedic patients and may lead to pulmonary embolism (PE) if the thrombus is dislodged. PE can be prevented by placing an inferior vena cava filter (IVCF) to intercept the dislodged thrombus. Thus, IVCFs play an important role in orthopaedics. However, the occurrence of complications after IVCF placement, particularly recurrent thromboembolism, makes it necessary to carefully assess the risk-benefit of filter placement. There is no accepted statement as to whether IVCF should be placed in orthopaedic patients. Based on the problems currently displayed in the use of IVCFs, an ideal IVCF is proposed that does not affect the vessel wall and haemodynamics and intercepts thrombi well. The biodegradable filters that currently exist come close to the description of an ideal filter that can reduce the occurrence of various complications. Currently available biodegradable IVCFs consist of various organic polymeric materials. Biodegradable metals have shown good performance in making biodegradable IVCFs. However, among the available experimental studies on degradable filters, there are no experimental studies on filters made of degradable metals. This article reviews the use of IVCFs in orthopaedics, the current status of filters and the progress of research into biodegradable vena cava filters and suggests possible future developments based on the published literature by an electronic search of PubMed and Medline databases for articles related to IVCFs searchable by October 2022 and a manual search for citations to relevant studies.